Analisis Pendapatan Petani Kentang Pada Program Food Estate Desa Ria-Ria Kecamatan Pollung Kabupaten Humbang Hasudutan - Banjarnahor, Yohanes Syahputra; Dalimunthe, Apip Gunaldi; Safitri, Sri Ariani (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
This study aims to maintain the economic, social, and political stability of a country and ensure that high-quality food is available, accessible to all people and increased domestic production. The problem is focused on the Indonesian Government launching a National food barn development strategy to overcome the food crisis through the "Food estate" Program. In North Sumatra, food estates are the right solution to increasing food security. By having a horticultural area, one of which is potato plants. This study analyzes with a descriptive quantitative approach using primary and secondary data. This study concludes that the average income of potato farmers reaches IDR 52,047,133 per year with an R / C ratio of 4.72, which is profitable, so there is a need for a program development strategy using the SWOT method, with an emphasis on technological innovation and increased collaboration at the local community level and large companies.